2013
DOI: 10.3109/09638288.2013.788218
|View full text |Cite
|
Sign up to set email alerts
|

An enriched environment increases activity in stroke patients undergoing rehabilitation in a mixed rehabilitation unit: a pilot non-randomized controlled trial

Abstract: This preliminary trial suggests that the comprehensive model of enrichment developed for use in a rehabilitation unit was effective in increasing activity in stroke patients and reducing time spent inactive and alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
203
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(213 citation statements)
references
References 46 publications
8
203
0
2
Order By: Relevance
“…1,3,4 Recent clinical studies have also shown that stroke rehabilitation in the early postacute phase is most effective when performed in an engaging environment that provides novel and multisensory stimulation. 25,26 This is further supported by studies showing additive effects of social activity, exercise, music, and dance on cognitive improvement in healthy elderly individuals and in patients with Parkinson disease. 10 In the present study, we show that sustained improvement can occur in late phase after stroke as a result of multimodal intervention.…”
Section: July 2017mentioning
confidence: 51%
See 1 more Smart Citation
“…1,3,4 Recent clinical studies have also shown that stroke rehabilitation in the early postacute phase is most effective when performed in an engaging environment that provides novel and multisensory stimulation. 25,26 This is further supported by studies showing additive effects of social activity, exercise, music, and dance on cognitive improvement in healthy elderly individuals and in patients with Parkinson disease. 10 In the present study, we show that sustained improvement can occur in late phase after stroke as a result of multimodal intervention.…”
Section: July 2017mentioning
confidence: 51%
“…3 Enriched environment includes several different components, such as social stimulation, sensorimotor and cognitive stimulation, and exercise. 2,4,25 Several studies show that enriched environment is more effective than any of the individual components in promoting recovery after brain injury. 1,3,4 Recent clinical studies have also shown that stroke rehabilitation in the early postacute phase is most effective when performed in an engaging environment that provides novel and multisensory stimulation.…”
Section: July 2017mentioning
confidence: 99%
“…417 Särkämö et al 442 performed a single-blind RCT to determine whether listening to music everyday can facilitate the recovery of cognitive functions after stroke. Two months of daily listening (95 minutes daily) to self-selected music after acute stroke improved verbal memory, focused attention, and depressive symptoms compared with listening to an audio book or not listening to music.…”
Section: Enriched Environmentmentioning
confidence: 99%
“…For example, tablet technology allows for patients to engage in cognitive exercises and games that can be tailored to their specific impairments and made progressively more challenging as they improve. Along these lines, Janssen et al [81] have reported encouraging preliminary results in a study where EE was incorporated into a stroke rehabilitation unit.…”
Section: Therapeutic Interventions Across the Lifespanmentioning
confidence: 92%